Fruit Characterization and Evaluation of Hybrids Mango (Mangifera Indica L.) - Husen, S. (International Journal of Engineering and Technology, 2019)
Variety improvement to get a unique and exotic mango being one of the mango breeding program in Indonesia. This study aims to perform the characterization and evaluation of mango hybrids by morphological characteristics and chemical properties as well as fruit yield. The material is 17 mango plants hybrid (F1),  3 years old,  the  cultivars from crosses Arumanis -143 (Cg-48) which has a green color on the fruit skin with 6 clones of Cukurgondang red mango. To find fruit diversity, 16 characters quantitative and 23 qualitative characters are observed using Descriptors for Mango of  The International Plant Genetic Resources Institute 2006,  and the evaluation done on the characters of  weight fruit, fruit pulp thickness, total soluble solids, fruit yield and fruit color. The results showed that the vast diversity only occur on characters of the weight of the fruit, seed and endocarp weight, while others have a narrow diversity. Principal component analysis on 23 qualitative characters of fruit formed 6 major components with the cumulative diversity of 81.9%, the highest proportion (PC1)  of 23.2%. which is the character of the shape of fruit apex, skin color of  ripe fruit, fiber length in the pulp, and cluster analysis of 13 genotypes formed two clusters. Evaluation of hybrid with high yield occur in F1-15 and F1-87, while high total dissolved solids occur in F1-02, F1-22, F1-49 and hybrid red fruit skin is F1-31, F1-47, F1-44 and F1-09 successively.